2019
DOI: 10.1007/s00167-019-05450-1
|View full text |Cite
|
Sign up to set email alerts
|

Age over 50 years is not a contraindication for anterior cruciate ligament reconstruction

Abstract: PurposeTo report clinical and functional results of ACL reconstruction in patients over 50 years old and investigate the influence of surgery on osteoarthritis progression in this cohort of patients. MethodsA systematic review was performed on PubMed, Scopus, Google scholar, Cochrane library and EMBASE, using a strategy search design to collect clinical studies reporting outcomes of ACL reconstruction in patients aged 50 years or older. The primary outcome measure was clinical and functional results, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 56 publications
(244 reference statements)
2
28
0
Order By: Relevance
“…At the time of failure, most did not undergo revision ACLR because of their age. Recent studies have reported good functional results after ACL surgery in older patients, 5 perhaps indicating that some of these patients may benefit from revision. Despite satisfying mean subjective scores (>80 out of 100), only one-third of the reviewed patients had a “forgotten knee.” 10…”
Section: Discussionmentioning
confidence: 99%
“…At the time of failure, most did not undergo revision ACLR because of their age. Recent studies have reported good functional results after ACL surgery in older patients, 5 perhaps indicating that some of these patients may benefit from revision. Despite satisfying mean subjective scores (>80 out of 100), only one-third of the reviewed patients had a “forgotten knee.” 10…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of ACLR in patients older than 50 years old found good results with all graft types, although only 65 patients (13.8% of their population) had BPTB allograft, and they did not stratify results by allograft source. 34 When considering ACLR in the older population, nonoperative treatment must certainly be considered. While many patients aged 50 and older may have acceptable function with a torn ACL, studies have shown that age alone is not a contraindication to ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of ACLR in patients older than 50 years old found good results with all graft types, although only 65 patients (13.8% of their population) had BPTB allograft, and they did not stratify results by allograft source. 34 …”
Section: Discussionmentioning
confidence: 99%
“…With an ever-increasing number of active individuals and increasing life expectancy, more and more patients are participating in high risk activities for ACL injury well into the later years of life. As a result, there has been an increasing number of studies evaluating the clinical outcomes of ACL reconstruction in older patients [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. While 40 years of age has traditionally been the cut off for older patients, several published case reports have documented satisfactory clinical outcomes in patients in their 70s and 80s [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%